Die schwierige Frage der Nutzung des Römischen Kaiserpalastes auf dem Palatin in Rom in der Spätantike - Wulf-Rheidt, Ulrike (Antiquité Tardive - Late Antiquity - Spätantike - Tarda Antichità, 2018)
Abstract As the last major building phase for the imperial palaces on the Palatine in Rome, large-scale reconstruction and modification can be documented in the 4th century AD, which can be dated by tile stamps to the reign of Diocletian at the earliest, but more probably to that of Maxentius. At the beginning of the 4th century, the south-eastern area of the so-called Domus Severiana was extended once again, and the Severan baths were substantially enlarged. There is also evidence for alterations to the Domus Augustana at this time. Brick-stamps show evidence of no further major building phase until the time of Theoderic around AD 500. Most likely, in the 5th century an amphitheatre was created in the so-called Garden Stadium, whose decoration must already have been destroyed by that time. For the 4th and 5th centuries, emperors’ sojourns on the Palatine are documented in literary sources, so that it can be assumed that parts of the Roman palace complex were still in use. Due to the excavation history, these late phases are difficult to reconstruct. On the basis of the limited literary and physical evidence, this article attempts to sketch the use of the once splendid palace complex up to the attested stay by Theoderic.